2003
DOI: 10.1161/01.cir.0000070937.52035.25
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Insulin Receptor Substrate-2 Causes Progressive Neointima Formation in Response to Vessel Injury

Abstract: Background-Insulin resistance is associated with atherosclerosis, but its mechanism is unknown. It has been reported that insulin receptor substrate (IRS)-1 deficient ( IRS-1 Ϫ/Ϫ ) mice showed insulin resistance without type 2 diabetes, whereas the IRS-2 deficient (IRS-2 Ϫ/Ϫ ) mice showed insulin resistance with type 2 diabetes. Methods and Results-We investigated neointima formation in the IRS-1 Ϫ/Ϫ and IRS-2 Ϫ/Ϫ mice at 8 and 20 weeks. The IRS-2 Ϫ/Ϫ mice showed much greater neointima formation than the IRS-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 22 publications
6
56
0
Order By: Relevance
“…Abe and coworkers (Abe et al, 1998) previously showed that IRS-1-deficient mice exhibit insulin resistance, hypertension, and impaired endothelium-derived relaxation. Furthermore, a comparison of endotheliumdependent relaxation responses among IRS-1-deficient, IRS-2-deficient, and wild-type mice (Kubota et al, 2003) revealed that relaxation was impaired in the IRS-2-deficient mice at 20 weeks, but not at 8 weeks. In addition, in the IRS-1-deficient mice there was a mild impairment of endothelium-dependent vascular relaxation at 20 weeks.…”
Section: Pi3-k/akt Pathway and Endothelial Dysfunction In Type II Diamentioning
confidence: 99%
“…Abe and coworkers (Abe et al, 1998) previously showed that IRS-1-deficient mice exhibit insulin resistance, hypertension, and impaired endothelium-derived relaxation. Furthermore, a comparison of endotheliumdependent relaxation responses among IRS-1-deficient, IRS-2-deficient, and wild-type mice (Kubota et al, 2003) revealed that relaxation was impaired in the IRS-2-deficient mice at 20 weeks, but not at 8 weeks. In addition, in the IRS-1-deficient mice there was a mild impairment of endothelium-dependent vascular relaxation at 20 weeks.…”
Section: Pi3-k/akt Pathway and Endothelial Dysfunction In Type II Diamentioning
confidence: 99%
“…Insulin receptor substrate-2 (Irs2) is the major insulin receptor substrate isoform expressed in endothelial cells (13). We previously reported that mice with the Irs2 deletion (knockout [KO]) in endothelial cells (ETIrs2KO mice) exhibited an attenuation of the insulin-induced capillary blood flow in skeletal muscle (14).…”
mentioning
confidence: 99%
“…Although IRS-1 is most important to insulin action in skeletal muscle, IRS-2 appears to be required for insulin/IGF-I and, importantly, cytokine signaling in liver, muscle, fat, pancreatic ␤ cells, B cells, T cells, and macrophages (9,(23)(24)(25). IRS-2 knock-out studies in mice have shown that IRS-2 is important for neuroendocrine function, and a lack of IRS-2 leads to enhanced neointima formation (26,27). Furthermore, IRS-2 is necessary for IL-4-induced proliferation and differentiation of T cells (28).…”
mentioning
confidence: 99%